Overview of the Effect of Complementary Obstetric Care of Guava Juice and the Application of Logbook to Increase Hb Levels - Pisnitri, Pisnitri; Nilawati, Iin; Herlinda, Herlinda; Elly, Nur (Jurnal Midpro, 2022)
Anemia in pregnancy is called "potential danger to mother and child" (potential harm to mother and child). According to the World Health Organization (WHO) in 2014 there are 52% of pregnant women experiencing anemia in developing countries, one of which is Indonesia. Prevention of anemia in pregnant women can be done in 2 ways, one of which is by pharmacological therapy by consuming Fe tablets and non-pharmacological therapy with red guava juice and the assistance of the application of pregnancy nutrition logbook. This study uses observational descriptive methods. This study aims to find out the effect of rising HB levels of pregnant women with severe anemia. This study was conducted for 4 months, based on research at each visit with the provision of guava juice and assistance in the application of pregnancy nutrition logbook average and an increase in Hb levels of 0.0925g% with an average increase in Hb levels per day of 0.03 gr%. The limitations of the authors in conducting this study are the cost and time of examination of Hb levels. This study can be beneficial for pregnant women who are severely anemic, students and educational institutions.